Some of The Field and Laboratory Studies on Grouting Properties for Weak Soils: A Review - Ali H. Shareef, Mohammed A. Al- Neami, Falah H. Rahil (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Weak soils must be stabilized to meet technical specifications so that the constructions may be installed without massive settlements. Soil stabilization has become one of the most helpful options for this. In the 1970s and 1980s, admixture-based ground remediation developed in Japan. It is less compressible and has a lower permeability coefficient than the original soil after treatment. One of the oldest and most common ways to improve soil is to add admixtures of chemical materials such as cement, lime or/and quicklime, bitumen, and oil. Soil cement is a substance that is created by mixing cement with soil. In the mid-1970s, Sweden and Japan concurrently developed the conventional approach described as deep mixing. Cementitious or other materials are mixed into the soil in this in-situ treatment method. The deep mixing may inject using a jet grouting approach where erosion and mixing of weak soils in situ using a fluid jet. The injection strategies are a viable soil enhancement technique for fragile soils. Methods may use to safeguard piling structures. End-bearing pile repairs that used jet grouting required a robust and rigid framework to distribute the stresses of the grouted pile evenly. Since it can be applied to any soil, jet grouting is an excellent method for safeguarding pile foundations. The ground qualities may improve via chemical stabilization, which involves putting chemicals into the soil. Additives often used in asphalt mixtures include cement, lime, fly ash, and asphalt. Some of these are sodium silicates, acrylamides, N-methylolacrylamides, polyurethanes, epoxy resin, aminoplast, phenoplast, and lignosulfonate, the most common chemicals utilized in chemical manufacturing today. This study has presented field and laboratory analysis of the characteristics of the injection, and the results suggest an improvement before and after the injection. However, numerous elements must be considered for soil enhancement, including the aim, desired soil strength, toxicity, and rheology.